As liberdades humanas como bases do desenvolvimento: Uma análise conceitual da abordagem das capacidades humanas de Amartya Sen - Maurício Mota Saboya Pinheiro (Instituto de Pesquisa Econômica Aplicada (IPEA), 2012)
– This text aims at making a conceptual analysis of the capabilities approach (development as freedom) proposed by the Indian economist and philosopher Amartya Sen. It seeks to provide a broad view on the conceptual web of Sen's approach; thereafter it points out some issues that are relevant to the assessment of institutions and public policies in general. This work should be understood as part of an ongoing and broader research that seeks to enlarge our analytical power to deal with the major problems of national development. To Amartya Sen, the more developed a country is, the more expanded is the horizon of its citizens' freedoms. So, Sen's analysis concerns what should be the true aim of development: persons themselves. In this sense, Sen's social evaluation approach is to be distinguished from the more traditional ones that focus on income, wealth and/or other means which people employ in order to attain their objectives. This work concludes that the capabilities approach may be seen as a general method of evaluating development strategies, institutions and public policies. Also, that Sen's ideas can contribute many insights and relevant information that could be combined with diagnoses and methods employed in the more traditional approaches.
Keywords: O15; 330; economic development; human development; freedom; Amartya Sen